KINERJA TENAGA KESEHATAN DALAM PELAYANAN PASIEN DI PUSKESMAS RANTAU PANJANG KIRI KECAMATAN KUBU KABUPATEN ROKAN HILIR - Desi Novrida Sari; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Health personnels are individuals who work or serve in health enough knowledge and skills as well as ever and learning of health education for all types of condition requires the authority to make health efforts. The importance of the service sector in the private and government institutions. how important quality of the service itself to make a lot of impact with good services sector in institutions can improve themselves and the achievement of the the quality service. This research aims to determine the performance of health personnel in patient care in the Rantau Panjang Kiri public health centre and to know the factors those influenced performance of health personnels in patient care in the Rantau Panjang Kiri public health centre.the Research uses qualitative method with descriptive research. This research uses the theory of performance indicators from Agus Dwiyanto those are productivity, not only measures the level of efficiency but also the effectiveness of services, quality of service, responsiveness needs of the society, responbilitas implementation of organization's activities, accountability for implementing the organization's activities to work as the leader asking or listen the assumptions of subordinate. the research uses observation technique, interview and documentation with using triangulation analysis technique.The result of this research indicates that the personnel health performance in patient care in hospitalization of the Rantau Panjang public health centre has been good, although not fully. This was valued by means the personnel serves society with good and friendly treatment, to public health centre can be the experience and can improve the performance of health personnels to attend trainings, increase the capacity of patient rooms and complementary facilities and infrastructure.Keywords : performance, service, pramedis